Analisis Fisika, Kimia, dan Biologi Sampel Air Minum Pancuran : (Studi Kasus Desa Lora, Kecamatan Mataoleo, Kabupaten Bombana, Provinsi Sulawesi Tenggara) - Irzalin, Irzalin; Rosdiana, Rosdiana; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
In this research, the main objective to determine the number of Coliform bacteria, pH, temperature and TSS found in shower water samples in Lora Village. The results of testing the physical properties of water represented by TSS exceed the quality standards with an average value of 313.33 mg/l. Meanwhile, the water temperature is still in accordance with quality standards, namely 2°C from environmental temperature. The chemical properties represented by pH show a value of 7, and the biological properties of the water sample, namely total coliforms of 29 jml/100 ml, this value is still in accordance with the quality standards according to PERMENKES No. 2 of 2023 concerning environmental health quality standards and water health requirements for hygienic and sanitation purposes. From the test results it can be concluded that the total coliform, pH and temperature tests still comply with quality standards. Meanwhile, TSS passes quality standards.